2018
DOI: 10.1111/jfbc.12692
|View full text |Cite
|
Sign up to set email alerts
|

Aptitude of sorghum ( Sorghum bicolor (L) Moench) hybrids for brewery or bio‐functional malted beverages

Abstract: The potential of twenty‐four hybrids of white (WS) and red sorghum (RS) to produce beer or bio‐functional malted beverages was studied. Brewery aptitude was evaluated through diastatic power (DP), β‐amylase activity, hot water extract (HWE), and Kolbach index using sorghum malted at 30°C; while bio‐functional potential was evaluated through GABA, free amino acids (FAA) content, phenolics, and antioxidant capacity of sorghum malted at 25°C. Only eight hybrids showed DP and β‐amylase activity appropriate to brew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Sorghum [Sorghum bicolor (L.) Moench] ranks fifth in the major grain crops in production, area harvested, and yield worldwide [1], and more than 300 million people use it as a staple food, particularly in developing semiarid tropical areas [2]. In addition to its use as a human food source, sorghum is also used for animal feed [3], brewery or bio-functional malted beverages [4], building materials [5], as a source of sweet syrup/juice [6], a source of bioactive metabolites [7], and for bioenergy [8]. It is a hardy crop, able to withstand both drought and flooding conditions, as well as produce high yields, making it a model crop for agricultural adaptation to climate change and human population growth [9].…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum [Sorghum bicolor (L.) Moench] ranks fifth in the major grain crops in production, area harvested, and yield worldwide [1], and more than 300 million people use it as a staple food, particularly in developing semiarid tropical areas [2]. In addition to its use as a human food source, sorghum is also used for animal feed [3], brewery or bio-functional malted beverages [4], building materials [5], as a source of sweet syrup/juice [6], a source of bioactive metabolites [7], and for bioenergy [8]. It is a hardy crop, able to withstand both drought and flooding conditions, as well as produce high yields, making it a model crop for agricultural adaptation to climate change and human population growth [9].…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum malt could provide higher content of bioactive compounds, such as phenolic acids and γ-aminobutyric acid. 10 Alternatively, it had been demonstrated that milk is a source of bioactive peptides with high antioxidant, antihypertensive and anti-diabetogenic activity, which also can be generated during gastrointestinal digestion. 11 As far as we know there are no studies that evaluate the effects of adding sorghum malt or skim milk to whole grain sorghum fermented products over bio-functional properties after a simulated gastrointestinal digestion, nor prebiotic properties of different kinds of fermented sorghum based products.…”
Section: Introductionmentioning
confidence: 99%
“…Whole sorghum grain fermented products could be nutritionally and functionally improved by adding malted sorghum or skim milk. Sorghum malt could provide higher content of bioactive compounds, such as phenolic acids and γ‐aminobutyric acid 10 . Alternatively, it had been demonstrated that milk is a source of bioactive peptides with high antioxidant, antihypertensive and anti‐diabetogenic activity, which also can be generated during gastrointestinal digestion 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, most of gluten free beers are prepared using commercial enzymes or adjuncts such as rice or extruded sorghum in order to supply amylolytic activity and substrates for fermentation (Ndubisi et al ., ; Ma et al ., ). Nevertheless, malted sorghum obtained in optimal conditions allows producing enough amylase activity and bioactive compounds (Garzón & Drago, ).…”
Section: Introductionmentioning
confidence: 99%